Impact of COVID-19 on mental health and academic activities of university students: A cross sectional study from Pakistan. - Samo, Ayaz Ali; Bibi Sayed, Raheela; Abbasi, Maidha; b, Nimra Masood; Nabi Bux, Sanobar (BioSight, 2022)
Introduction: Mental health is essential for wellbeing. Mental health issues may affect the lives of students in several ways. COVID-19 pandemic has negatively affected the mental health of students. Previously conducted studies from Pakistan have just focused on prevalence of mental health problems and such studies could not relate the mental health problems with academic activities. The objective of this study was to associate COVID-19 affected mental health with academic activities among university students. Methods: This cross-sectional study was conducted during month of April 2021 at university of Sindh, Pakistan. After obtaining informed consent form study participants a pretested questionnaire was distributed to collect demographic and mental health data. Depression, Anxiety, Stress Scale (DASS-21) was used to assessment of depression, anxiety, and stress. Cronbach’s alpha value for DASS-21 was 0.84. Results: Among total of 400 study participants, 49% were females and 51% were males. The mean age of study participants was 20.9±1.06 years. Overall prevalence of mild to severe stress, anxiety, and depression was 14.8%, 10.5% and 18.8% respectively. Among demographic factors female having less amount for pocket money was associated with increased prevalence of stress and anxiety respectively. Academic factors such as unable to focus, difficulties in completing assignments and facing internet connectivity problems were associated with increased prevalence of anxiety, stress, and depression. Conclusion: COVID-19 have negatively impacted the mental health of university students. There is need of chalking out scientific strategies to launch psychosocial support programs for students to teach them coping skills against mental health problems.